A round-robin finite element analysis of human femur mechanics between seven participating laboratories with experimental validation. Issue 12 (10th September 2019) - Kluess, Daniel; Soodmand, Ehsan; Lorenz, Andrea; Pahr, Dieter; Schwarze, Michael; Cichon, Robert; Varady, Patrick A.; Herrmann, Sven; Buchmeier, Bernhard; Schröder, Christian; Lehner, Stefan; Kebbach, Maeruan
Abstract: Finite element analysis is a common tool that has been used for the past few decades to predict the mechanical behavior of bone. However, to our knowledge, there are no round-robin finite element analyses of long human bones with more than two participating biomechanics laboratories published yet, where the results of the experimental tests were not known in advance. We prepared a fresh-frozen human femur for a compression test in a universal testing machine measuring the strains at 10 bone locations as well as the deformation of the bone in terms of the displacement of the loading point at a load of 2 kN. The computed tomography data of the bone with a calibration phantom as well as the orientation of the bone in the testing machine with the according boundary conditions were delivered to seven participating laboratories. These were asked to perform a finite element analysis simulating the experimental setup and deliver their results to the coordinator without knowing the experimental results. Resultantly, four laboratories had deviations from the experimentally measured strains of less than 40%, and three laboratories had deviations of their numerically determined values compared to the experimental data of more than 120%. These deviations are thought to be based on different material laws and material data, as well as different material mapping methods. Investigations will be conducted to clarify and assess the reasons for the large deviations in the numerical data. It was shown that the precision of finite element models of the human femur is not yet as developed as desired by the biomechanics community.